Multiscale time-resolved fluorescence study of a glycogen phosphorylase inhibitor combined with quantum chemistry calculations - Maffeis, Valentin; Mavreas, Konstantinos; Monti, Filippo; Mamais, Michael; Gustavsson, Thomas; Chrysina, Evangelia D.; Markovitsi, Dimitra; Gimisis, Thanasis; Venturini, Alessandro (Physical Chemistry Chemical Physics, 2019)
A fluorescence study of N1-(β-D-glucopyranosyl)-N4-[2-acridin-9(10H)-onyl]-cytosine (GLAC), the first fluorescent potent inhibitor of Glycogen Phosphorylase (GP), in neutral aqueous solution, is presented herein. Quantum chemistry (TD-DFT) calculations show the existence of several conformers both in the ground and first excited state. They result from rotation of the acridone and cytosine moieties around an NH bridge which may lead to the formation of non-emitting charge transfer states. The fingerprint of various conformers have been detected by time-resolved fluorescence spectroscopy (fluorescence upconversion and time-correlated single photon counting) and identified using as criteria their energy, polarization and relative population resulting from computations. Such an analysis should contribute to the design of new GP inhibitors with better fluorescence properties, suitable for imaging applications.